Zodiac : a graphic memoir - Ai, Weiwei; Stamboulis, Elettra (Ten Speed Graphic, an imprint of the Crown Publishing Group, 2024)
"As a child living in exile during the Cultural Revolution, Ai Weiwei often found himself with nothing to read but government-approved comic books. Although they were restricted by the confines of political propaganda, Ai Weiwei was struck by the artists' ability to express their thoughts on art and humanity through graphic storytelling. Now, decades later, Ai Weiwei and Italian comic artist Gianluca Costantini present Zodiac, Ai Weiwei's first graphic memoir. Inspired by the twelve signs of the Chinese zodiac and their associated human characteristics, Ai Weiwei masterfully interweaves ancient Chinese folklore with stories of his life, family, and career. The narrative shifts back and forth through the years--at once in the past, present, and future--mirroring memory and our relationship to time. As readers delve deeper into the beautifully illustrated pages of Zodiac, they will find not only a personal history of Ai Weiwei and an examination of the sociopolitical climate in which he makes his art, but a philosophical exploration of what it means to find oneself through art and freedom of expression."--Amazon.